A method for immunomagnetic enhanced detection of silk fibroin
Through the immunomagnetic enhancement detection method, combined with antigen antibodies and pressure sensors, nano CuO and functionalized nanomagnetic beads, the problem of silk fibroin detection in silk cultural relics in the prior art was solved, and the detection effect of high specificity and low detection limit was achieved.
Patent Information
- Application Number
- CN202210537942.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-18
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-05-18
AI Technical Summary
The prior art is difficult to effectively detect silk fibroin in silk cultural relics, especially under trace protein content, which has problems with low detection limit and high specificity.
The immunomagnetic enhancement detection method is used to significantly improve the detection efficiency and specificity by combining antigen antibodies and pressure sensors.
High specific detection of silk fibroin is achieved, which reduces the detection limit and can accurately detect under trace protein content, significantly improving the detection efficiency.
Abstract
Description
Technical Field
[0001] The invention relates to the field of cultural relics detection, and in particular to a method for immunomagnetic enhanced detection of silk fibroin. Background Art
[0002] China's textile culture has a long history. As an important channel for China's foreign cultural exchanges, the Silk Road has made a significant contribution to China's development history. The unearthed silk cultural relics also play a vital role in China's historical and cultural research. Therefore, studying the various representation methods of various silk cultural relics is the key point in the study of Chinese silk culture.
[0003] Silk cultural relics are difficult to protect intact during the long burial process. Due to various aging mechanisms, the characterization of silk is very difficult. When its structure is destroyed, various characterization results will lose their original characteristics. The farther away the discovered tomb is from us, the fewer silk fragments can be preserved and the more interferences there will be. Therefore, low detection limit and high specificity are the key to silk research. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for detecting silk fibroin by immunomagnetic enhancement. The present invention combines antigen antibody with a pressure sensor to provide a silk fibroin detection method with the advantages of immunospecificity, which has stronger specificity and lower detection limit.
[0005] The specific technical solution of the present invention is: a method for immunomagnetic enhanced detection of silk fibroin, comprising the following steps:
[0006] Step 1: Dissolve CuCl2·2H2O in water containing PEG to obtain a mixed solution, and disperse it evenly by ultrasonication; separately dissolve NaOH in a mixed solution of PEG and water, and disperse it evenly by ultrasonication; mix the two mixed solutions to react to obtain a CuO solution, further ultrasonicate it, add excess ethanol and let it stand; wash the product with anhydrous ethanol and water in turn, and titrate it with AgNO3 solution until Cl -1 Completely remove; then centrifuge the product to separate CuO, keep the product warm, grind it into powder, and calcine it at high temperature to obtain nano CuO.
[0007] Step 2: Weigh FeCl3·6H2O and FeSO4·7H2O, dissolve them in water, and stir them under nitrogen protection until dissolved; add NaOH to control the size, heat in a water bath and continue stirring to obtain Fe3O4 magnetic nanoparticles; weigh Fe3O4 magnetic nanoparticles in a container, add concentrated nitric acid, ultrasonically treat, then wash with water, add anhydrous ethanol, water and ammonia water, and then ultrasonically treat, take out, slowly add TEOS dropwise while stirring, continue stirring, then wash with ethanol and water in turn, vacuum dry to obtain nanomagnetic beads, and store them in phosphate buffer solution.
[0008] The function of TEOS is that it can be hydrolyzed under alkaline conditions to obtain silica-coated magnetic beads, thereby preventing the magnetic beads from reacting with acid.
[0009] Step 3: Put the nanomagnetic beads in a container, add water, and disperse them evenly by ultrasonication. Then add chloroform, anhydrous ethanol, and then add acrylamide, acetonitrile and methacrylic acid. Stir rapidly at room temperature. After fully mixing, add the initiator azobisisobutyronitrile, stir rapidly to react, use an external magnetic field for solid-liquid separation, wash repeatedly with anhydrous ethanol and water until excess organic matter is washed away to obtain functionalized nanomagnetic beads. Place them in 350-450uLPBS to obtain a functionalized nanomagnetic bead dispersion.
[0010] In the present invention, acrylamide, acetonitrile and methacrylic acid are added in step 3 as organic synthesis raw materials, so that the magnetic beads have flocculation properties for proteins, which can further enhance the ability of the magnetic beads to bind proteins and reduce the detection limit, so that even trace amounts of protein can be detected.
[0011] Step 4: Take the functionalized nanomagnetic bead dispersion particles in a centrifuge tube, wash them with phosphate buffer solution, and redisperse them in phosphate buffer solution; add EDC / NHS mixed solution to the obtained dispersion, activate the reaction by shaking at room temperature, wash them with phosphate buffer solution, disperse them in phosphate buffer, add silk fibroin antibody and shake them, then add Tris-BSA, shake and wash them to obtain specific magnetic beads, and disperse them in phosphate buffer.
[0012] Step 5: Take the nano-CuO obtained in step 1 and ultrasonically treat it in PBS, add silk protein antibody, shake it, freeze-centrifuge the obtained product, remove the upper clear liquid, disperse it in PBS, freeze-centrifuge it again, remove the lower substrate, add BSA solution, mix and react, and obtain specific nano-CuO.
[0013] Step 6: Add the obtained specific magnetic beads and specific nano-CuO to the silk fibroin solution to be tested, incubate with shaking, remove the supernatant after centrifugation, place it in hydrogen peroxide, pass the obtained oxygen into the pressure sensor, obtain its resistance change through the pressure change, and finally obtain the concentration of silk fibroin.
[0014] Preferably, step 1 is specifically as follows: dissolving CuCl2·2H2O in water containing 0.5-1.5wt% PEG, wherein the concentration of CuCl2 is 0.5-1.5wt%, to obtain a mixed solution, and uniformly dispersing the solution by ultrasonication; separately dissolving NaOH in water containing 0.5-1.5wt% PEG, to obtain a mixed solution, wherein the concentration of NaOH is 8-12mg / mL, and uniformly dispersing the solution by ultrasonication; mixing the two mixed solutions, further ultrasonically treating the mixture, adding excess ethanol, and standing the mixture overnight; washing the resultant with anhydrous ethanol and water in turn, and titrating the mixture with AgNO3 solution until Cl -1 Completely remove; then centrifuge the product, keep the product at 90-100℃ for 10-20h, grind it into powder, and calcine it at 350-450℃ to obtain nano CuO.
[0015] Preferably, step 2 is specifically as follows: weigh 5-6g FeCl3·6H2O and 2-4g FeSO4·7H2O, dissolve them in 100mL water, and stir them under nitrogen protection until dissolved; add 3-5g NaOH, and stir continuously in a 70-90°C water bath for 0.5-1.5h to obtain Fe3O4 magnetic nanoparticles; weigh 180-220mg Fe3O4 magnetic nanoparticles in a container, add 15-20mL concentrated nitric acid, ultrasonicate for 10-30min, then wash with water, add 15-25mL anhydrous ethanol, 35-45mL water and 3-5mL ammonia water, and then ultrasonicate for 10-30min, take out, slowly add 3-4mL TEOS dropwise while stirring, stir continuously for 3-5h, then wash with ethanol and water successively, and vacuum dry at 55-65°C for 1-3h to obtain nanomagnetic beads, which are stored in phosphate buffer solution.
[0016] Preferably, step 3 is specifically as follows: 0.3-0.5g of nanomagnetic beads are placed in a container, 15-25mL of water is added, ultrasonic dispersion is uniformly performed, 8-12mL of chloroform, 2-3mL of anhydrous ethanol are added, and then 0.3-0.7g of acrylamide, 0.8-1.2mL of acetonitrile and 2-3mL of methacrylic acid are added, and rapid stirring is performed at room temperature for 10-30min. After sufficient mixing, 0.08-0.12g of initiator azobisisobutyronitrile is added, and the reaction is rapidly stirred at 40-50°C for 6-8h, and solid-liquid separation is performed using an external magnetic field, and the beads are repeatedly washed with anhydrous ethanol and water until excess organic matter is washed away to obtain functionalized nanomagnetic beads. The particles are placed in 350-450uL PBS to obtain a functionalized nanomagnetic bead dispersion.
[0017] Preferably, step 4 is specifically as follows: take 80-120uL of functionalized nanomagnetic bead dispersion in a centrifuge tube, wash with phosphate buffer solution, and redisperse in 350-450uL phosphate buffer solution; add 250-350uL of EDC / NHS mixed solution to the obtained dispersion, activate the reaction by shaking at room temperature for 0.5-1.5h, wash with phosphate buffer solution, disperse in 400-600uL phosphate buffer, add 8-12uL silk fibroin antibody, shake at 25-30℃ for 0.5-1.5h, then add 80-120uL Tris-BSA, shake for 0.5-1.5h and then wash to obtain specific magnetic beads, which are dispersed in 300-500uL buffer.
[0018] Furthermore, in step 4, the pH value of the phosphate buffer solution is 7.4, and the usage ratio of MES, NaCl, EDC, and NHS in the EDC / NHS mixed solution is (0.3-0.5) g: (0.4-0.6) g: (15-25) mg: (20-30) mg.
[0019] Preferably, step 5 is specifically as follows: 0.8-1.2 mg of the nano-CuO obtained in step 1 is ultrasonically treated in 0.8-1.2 mL PBS for 0.5-1.5 h, 80-120 uL of silk fibroin antibody is added, and the mixture is shaken for 3-5 h. The obtained product is centrifuged and the upper clear liquid is removed, and the mixture is dispersed in 0.8-1.2 mL PBS, and the lower substrate is removed after centrifugation, and 300-500 uL of 2-4 wt% BSA solution is added, and the mixture is mixed and reacted for 20-40 min to obtain specific nano-CuO.
[0020] Preferably, step 6 is as follows: adding the obtained specific magnetic beads and specific nano-CuO to the silk fibroin solution, incubating with shaking at 30-40°C for 1-3h, removing the supernatant after centrifugation, placing in hydrogen peroxide, and passing the obtained oxygen into a pressure sensor to obtain a resistance change due to the pressure change, thereby obtaining the silk fibroin concentration.
[0021] Compared with the prior art, the present invention has the following technical effects:
[0022] (1) Due to the specific binding of antigen and antibody, the present invention can eliminate the interference of various impurities and improve the detection specificity and accuracy.
[0023] (2) The present invention utilizes the principle of CuO catalyzing hydrogen peroxide to significantly improve detection efficiency.
[0024] (3) The present invention utilizes the paramagnetism of magnetic beads to better separate the synthesized materials from the reaction system, thereby facilitating the washing and purification of the synthesized materials. DETAILED DESCRIPTION
[0025] The present invention will be further described below in conjunction with the embodiments.
[0026] Example 1
[0027] Step 1: Dissolve CuCl2·2H2O in water containing 1wt% PEG400 to obtain a mixed solution with a CuCl2 concentration of 1wt% and dispersed evenly by ultrasonication; separately dissolve NaOH in water containing 1wt% PEG400 to obtain a mixed solution with a NaOH concentration of 10mg / mL and dispersed evenly by ultrasonication; mix the two mixed solutions and further ultrasonicate them, add excess ethanol and let stand overnight; wash the resultant with anhydrous ethanol and water in turn, and titrate with AgNO3 solution until Cl -1 The product was then centrifuged and kept at 95°C for 12 hours, ground into powder, and calcined at 400°C to obtain nano-CuO.
[0028] Step 2: Weigh 5.5g FeCl3·6H2O and 3g FeSO4·7H2O and dissolve them in 100mL water, and stir until dissolved under nitrogen protection; add 4g NaOH, and continue stirring in a water bath at 80℃ for 1h to obtain Fe3O4 magnetic nanoparticles; weigh 200mg Fe3O4 magnetic nanoparticles in a container, add 18mL concentrated nitric acid, ultrasonicate for 20min, then wash with water, add 20mL anhydrous ethanol, 40mL water and 4mL ammonia water, and then ultrasonicate for 25min, take out, slowly add 3.6mL TEOS dropwise while stirring, continue stirring for 4h, then wash with ethanol and water successively, vacuum dry at 60℃ for 2h to obtain nanomagnetic beads, and store them in pH7.4 phosphate buffer solution.
[0029] Step 3: Take 0.4g of nanomagnetic beads in a container, add 20mL of water, ultrasonically disperse evenly, then add 10mL of chloroform, 2.5mL of anhydrous ethanol, then add 0.5g of acrylamide, 1.0mL of acetonitrile and 2.5mL of methacrylic acid, stir rapidly for 20min at room temperature, after fully mixing, add 0.1g of initiator azobisisobutyronitrile, stir rapidly at 45°C for 7h, use an external magnetic field for solid-liquid separation, wash repeatedly with anhydrous ethanol and water until the excess organic matter is washed away, and the functionalized nanomagnetic beads are placed in 400uL PBS to obtain a functionalized nanomagnetic bead dispersion.
[0030] Step 4: Take 100uL of functionalized nanomagnetic bead dispersion in a centrifuge tube, wash with pH 7.4 phosphate buffer solution, and redisperse in 400uL pH 7.4 phosphate buffer solution; add 300uL of EDC / NHS mixed solution (the dosage ratio of MES, NaCl, EDC, and NHS is (0.4)g: (0.5)g: (20)mg: (25)mg) to the obtained dispersion, activate the reaction at room temperature for 1h, wash with pH 7.4 phosphate buffer solution, disperse in 400-600uL pH 7.4 phosphate buffer, add 10uL silk fibroin 4522 antibody, shake at 27°C for 1h, then add 100uL Tris-BSA, shake for 1h, wash, and obtain specific magnetic beads, which are dispersed in 400uL phosphate buffer.
[0031] Step 5: Take 1.0 mg of the nano-CuO obtained in step 1 and ultrasonically treat it in 1.0 mL PBS for 1 h, add 100 uL of silk fibroin 5527 antibody, shake for 4 h, freeze-centrifuge the resulting product and remove the upper supernatant, disperse it in 1.0 mL PBS, freeze-centrifuge it again and remove the lower substrate, add 400 uL of 3 wt% BSA solution, mix and react for 30 min to obtain specific nano-CuO.
[0032] Step 6: Add 400uL of the obtained specific magnetic beads and 400uL of specific nano-CuO to 0.01g / mL, 0.001g / mL, and 0.0001g / mL silk fibroin solutions, respectively, incubate with shaking at 37°C for 2h, remove the supernatant after centrifugation, place in hydrogen peroxide, and pass the obtained oxygen into the pressure sensor.
[0033] The test results are as follows: the resistance of 0.01g / mL silk fibroin solution is 32.67kΩ, the resistance of 0.001g / mL silk fibroin solution is 38.56kΩ, and the resistance of 0.0001g / mL silk fibroin solution is 42.67kΩ. The above data show that the specific magnetic beads and specific nano-CuO obtained in Example 1 can detect silk fibroin in 0.01g / mL, 0.001g / mL, and 0.0001g / mL silk fibroin solutions.
[0034] Comparative Example 1 (the only difference from Example 1 is that non-functionalized immunomagnetic beads are used)
[0035] Step 1: Dissolve CuCl2·2H2O in water containing 1wt% PEG400 to obtain a mixed solution with a CuCl2 concentration of 1wt% and dispersed evenly by ultrasonication; separately dissolve NaOH in water containing 1wt% PEG400 to obtain a mixed solution with a NaOH concentration of 10mg / mL and dispersed evenly by ultrasonication; mix the two mixed solutions and further ultrasonicate them, add excess ethanol and let stand overnight; wash the resultant with anhydrous ethanol and water in turn, and titrate with AgNO3 solution until Cl -1 The product was then centrifuged and kept at 95°C for 12 hours, ground into powder, and calcined at 400°C to obtain nano-CuO.
[0036] Step 2: Weigh 5.5g FeCl3·6H2O and 3g FeSO4·7H2O and dissolve them in 100mL water, and stir until dissolved under nitrogen protection; add 4g NaOH, and continue stirring in a water bath at 80℃ for 1h to obtain Fe3O4 magnetic nanoparticles; weigh 200mg Fe3O4 magnetic nanoparticles in a container, add 18mL concentrated nitric acid, ultrasonicate for 20min, then wash with water, add 20mL anhydrous ethanol, 40mL water and 4mL ammonia water, and then ultrasonicate for 25min, take out, slowly add 3.6mL TEOS dropwise while stirring, continue stirring for 4h, then wash with ethanol and water successively, vacuum dry at 60℃ for 2h to obtain nanomagnetic beads, and store them in pH7.4 phosphate buffer solution.
[0037] Step 3: Take 100uL of nanomagnetic bead dispersion in a centrifuge tube, wash with pH 7.4 phosphate buffer solution, and redisperse in 400uL pH 7.4 phosphate buffer solution; add 300uL of EDC / NHS mixed solution (the dosage ratio of MES, NaCl, EDC, and NHS is (0.4)g: (0.5)g: (20)mg: (25)mg) to the obtained dispersion, activate the reaction at room temperature for 1h, wash with pH 7.4 phosphate buffer solution, disperse in 400-600uL pH 7.4 phosphate buffer, add 10uL silk fibroin 4522 antibody, shake at 27°C for 1h, then add 100uL Tris-BSA, shake for 1h, wash, and obtain specific magnetic beads, which are dispersed in 400uL phosphate buffer.
[0038] Step 4: Take 1.0 mg of the nano-CuO obtained in step 1 and ultrasonically treat it in 1.0 mL PBS for 1 h, add 100 uL of silk fibroin 5527 antibody, shake for 4 h, freeze-centrifuge the resulting product and remove the upper supernatant, disperse it in 1.0 mL PBS, freeze-centrifuge it again and remove the lower substrate, add 400 uL of 3 wt% BSA solution, mix and react for 30 min to obtain specific nano-CuO.
[0039] Step 5: Add 400uL of the obtained specific magnetic beads and 400uL of specific nano-CuO to 0.01g / mL, 0.001g / mL, and 0.0001g / mL silk fibroin solutions, respectively, incubate with shaking at 37°C for 2h, remove the supernatant after centrifugation, place in hydrogen peroxide, and pass the obtained oxygen into the pressure sensor.
[0040] The test results show that the resistance of 0.01g / ml silk fibroin solution is 49.67kΩ, while the resistance of 0.0001g / mL silk fibroin solution is close to the original resistance of the sensor 61.27kΩ. Therefore, it is shown that the detection limit of Comparative Example 1 is higher than 0.0001g / mL, revealing that the detection limit of the non-functional magnetic beads is higher than that of Example 1 using functionalized magnetic beads.
[0041] Example 2
[0042] Step 1: Dissolve CuCl2·2H2O in water containing 1wt% PEG400 to obtain a mixed solution with a CuCl2 concentration of 1wt% and dispersed evenly by ultrasonication; separately dissolve NaOH in water containing 1wt% PEG400 to obtain a mixed solution with a NaOH concentration of 10mg / mL and dispersed evenly by ultrasonication; mix the two mixed solutions and further ultrasonicate them, add excess ethanol and let stand overnight; wash the resultant with anhydrous ethanol and water in turn, and titrate with AgNO3 solution until Cl -1 The product was then centrifuged and kept at 95°C for 12 hours, ground into powder, and calcined at 400°C to obtain nano-CuO.
[0043] Step 2: Weigh 5.5g FeCl3·6H2O and 3g FeSO4·7H2O and dissolve them in 100mL water, and stir until dissolved under nitrogen protection; add 4g NaOH, and continue stirring in a water bath at 80℃ for 1h to obtain Fe3O4 magnetic nanoparticles; weigh 200mg Fe3O4 magnetic nanoparticles in a container, add 18mL concentrated nitric acid, ultrasonicate for 20min, then wash with water, add 20mL anhydrous ethanol, 40mL water and 4mL ammonia water, and then ultrasonicate for 25min, take out, slowly add 3.6mL TEOS dropwise while stirring, continue stirring for 4h, then wash with ethanol and water successively, vacuum dry at 60℃ for 2h to obtain nanomagnetic beads, and store them in pH7.4 phosphate buffer solution.
[0044] Step 3: Take 0.4g of nanomagnetic beads in a container, add 20mL of water, ultrasonically disperse evenly, then add 10mL of chloroform, 2.5mL of anhydrous ethanol, then add 0.5g of acrylamide, 1.0mL of acetonitrile and 2.5mL of methacrylic acid, stir rapidly for 20min at room temperature, after fully mixing, add 0.1g of initiator azobisisobutyronitrile, stir rapidly at 45°C for 7h, use an external magnetic field for solid-liquid separation, wash repeatedly with anhydrous ethanol and water until the excess organic matter is washed away, and the functionalized nanomagnetic beads are placed in 400uL PBS to obtain a functionalized nanomagnetic bead dispersion.
[0045] Step 4: Take 100uL of functionalized nanomagnetic bead dispersion in a centrifuge tube, wash with pH 7.4 phosphate buffer solution, and redisperse in 400uL pH 7.4 phosphate buffer solution; add 300uL of EDC / NHS mixed solution (the dosage ratio of MES, NaCl, EDC, and NHS is (0.4)g: (0.5)g: (20)mg: (25)mg) to the obtained dispersion, activate the reaction at room temperature for 1h, wash with pH 7.4 phosphate buffer solution, disperse in 400-600uL pH 7.4 phosphate buffer, add 10uL silk fibroin 4522 antibody, shake at 27°C for 1h, then add 100uL Tris-BSA, shake for 1h, wash, and obtain specific magnetic beads, which are dispersed in 400uL phosphate buffer.
[0046] Step 5: Take 1.0 mg of the nano-CuO obtained in step 1 and ultrasonically treat it in 1.0 mL PBS for 1 h, add 100 uL of silk fibroin 5527 antibody, shake for 4 h, freeze-centrifuge the resulting product and remove the upper supernatant, disperse it in 1.0 mL PBS, freeze-centrifuge it again and remove the lower substrate, add 400 uL of 3 wt% BSA solution, mix and react for 30 min to obtain specific nano-CuO.
[0047] Step 6: Add 400uL of the obtained specific magnetic beads and 400uL of specific nano-CuO into five silk fibroin solutions of 100ng / mL, 10ng / mL, 1ng / mL, 0.1ng / mL, and 0.01ng / mL, respectively, incubate with shaking at 37°C for 2h, remove the supernatant after centrifugation, place in hydrogen peroxide, and pass the obtained oxygen into the pressure sensor to obtain resistance change due to its pressure change.
[0048] The test results are as follows: the resistance of 100ng / mL silk fibroin solution is 46.37kΩ, the resistance of 10ng / mL silk fibroin solution is 49.65kΩ, the resistance of 1ng / mL silk fibroin solution is 52.32kΩ, the resistance of 0.1ng / mL silk fibroin solution is 56.78kΩ, and the resistance of 0.01ng / mL is 59.49kΩ. The above data show that the specific magnetic beads and specific nano-CuO obtained in Example 1 can detect silk fibroin in five concentrations of 100ng / mL, 10ng / mL, 1ng / mL, 0.1ng / mL, and 0.01ng / mL silk fibroin solutions.
[0049] Example 3
[0050] Step 1: Dissolve CuCl2·2H2O in water containing 1wt% PEG400 to obtain a mixed solution with a CuCl2 concentration of 1wt% and dispersed evenly by ultrasonication; separately dissolve NaOH in water containing 1wt% PEG400 to obtain a mixed solution with a NaOH concentration of 10mg / mL and dispersed evenly by ultrasonication; mix the two mixed solutions and further ultrasonicate them, add excess ethanol and let stand overnight; wash the resultant with anhydrous ethanol and water in turn, and titrate with AgNO3 solution until Cl -1 The product was then centrifuged and kept at 95°C for 12 hours, ground into powder, and calcined at 400°C to obtain nano-CuO.
[0051] Step 2: Weigh 5.5g FeCl3·6H2O and 3g FeSO4·7H2O and dissolve them in 100mL water, and stir until dissolved under nitrogen protection; add 4g NaOH, and continue stirring in a water bath at 80℃ for 1h to obtain Fe3O4 magnetic nanoparticles; weigh 200mg Fe3O4 magnetic nanoparticles in a container, add 18mL concentrated nitric acid, ultrasonicate for 20min, then wash with water, add 20mL anhydrous ethanol, 40mL water and 4mL ammonia water, and then ultrasonicate for 25min, take out, slowly add 3.6mL TEOS dropwise while stirring, continue stirring for 4h, then wash with ethanol and water successively, vacuum dry at 60℃ for 2h to obtain nanomagnetic beads, and store them in pH7.4 phosphate buffer solution.
[0052] Step 3: Take 0.4g of nanomagnetic beads in a container, add 20mL of water, ultrasonically disperse evenly, then add 10mL of chloroform, 2.5mL of anhydrous ethanol, then add 0.5g of acrylamide, 1.0mL of acetonitrile and 2.5mL of methacrylic acid, stir rapidly for 20min at room temperature, after fully mixing, add 0.1g of initiator azobisisobutyronitrile, stir rapidly at 45°C for 7h, use an external magnetic field for solid-liquid separation, wash repeatedly with anhydrous ethanol and water until the excess organic matter is washed away, and the functionalized nanomagnetic beads are placed in 400uL PBS to obtain a functionalized nanomagnetic bead dispersion.
[0053] Step 4: Take 100uL of functionalized nanomagnetic bead dispersion in a centrifuge tube, wash with pH 7.4 phosphate buffer solution, and redisperse in 400uL pH 7.4 phosphate buffer solution; add 300uL of EDC / NHS mixed solution (the dosage ratio of MES, NaCl, EDC, and NHS is (0.4)g: (0.5)g: (20)mg: (25)mg) to the obtained dispersion, activate the reaction at room temperature for 1h, wash with pH 7.4 phosphate buffer solution, disperse in 400-600uL pH 7.4 phosphate buffer, add 10uL silk fibroin 4522 antibody, shake at 27°C for 1h, then add 100uL Tris-BSA, shake for 1h, wash, and obtain specific magnetic beads, which are dispersed in 400uL phosphate buffer.
[0054] Step 5: Take 1.0 mg of the nano-CuO obtained in step 1 and ultrasonically treat it in 1.0 mL PBS for 1 h, add 100 uL of silk fibroin 5527 antibody, shake for 4 h, freeze-centrifuge the resulting product and remove the upper supernatant, disperse it in 1.0 mL PBS, freeze-centrifuge it again and remove the lower substrate, add 400 uL of 3 wt% BSA solution, mix and react for 30 min to obtain specific nano-CuO.
[0055] Step 6: Add 400uL of the obtained specific magnetic beads and 400uL of specific nano-CuO to 5mL of 0.001g / mL silk fibroin solution and 5mL of 0.001g / mL wool keratin solution respectively, incubate with shaking at 37°C for 2h, remove the supernatant after centrifugation, place in hydrogen peroxide, and pass the obtained oxygen into the pressure sensor.
[0056] The test results show that the resistance of the silk fibroin solution is 38.56 kΩ, and the resistance of the wool keratin solution is 61.28 kΩ, which is close to the original resistance of the sensor of 61.27 kΩ. This shows that this embodiment is specific to silk fibroin and cannot be used to detect wool keratin.
[0057] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0058] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for immunomagnetic enhanced detection of silk fibroin, characterized in that The steps include: Step 1: Dissolve CuCl2·2H2O in water containing PEG to obtain a mixed solution, and disperse it evenly by ultrasonication; separately dissolve NaOH in a mixed solution of PEG and water, and disperse it evenly by ultrasonication; mix the two mixed solutions to obtain a CuO solution, further ultrasonicate it, add excess ethanol and let it stand; wash the product with anhydrous ethanol and water in turn, and titrate it with AgNO3 solution until Cl -1 Completely remove; then centrifuge the product, keep the product warm, grind it into powder, and calcine it at high temperature to obtain nano CuO; Step 2: weigh FeCl3·6H2O and FeSO4·7H2O, dissolve them in water, and stir them under nitrogen protection until dissolved; add NaOH, heat in a water bath and continue stirring to obtain Fe3O4 magnetic nanoparticles; weigh Fe3O4 magnetic nanoparticles in a container, add concentrated nitric acid, ultrasonically treat, then wash with water, add anhydrous ethanol, water and ammonia water, and then ultrasonically treat, take out, slowly add TEOS dropwise while stirring, continue stirring, then wash with ethanol and water in succession, vacuum dry, obtain nano magnetic beads, and store them in phosphate buffer solution; Step 3: Put the nano magnetic beads in a container, add water, disperse them evenly by ultrasonication, then add chloroform, anhydrous ethanol, then add acrylamide, acetonitrile and methacrylic acid, stir rapidly at room temperature, mix thoroughly, add initiator azobisisobutyronitrile, stir rapidly to react, use an external magnetic field for solid-liquid separation, wash repeatedly with anhydrous ethanol and water until excess organic matter is washed away, obtain functionalized nano magnetic beads, place in 350-450uL PBS, and obtain functionalized nano magnetic beads dispersion; Step 4: Take the functionalized nanomagnetic bead dispersion in a centrifuge tube, wash it with a phosphate buffer solution, and redisperse it in a phosphate buffer solution; add the EDC / NHS mixed solution to the obtained dispersion, activate the reaction by shaking at room temperature, wash it with a phosphate buffer solution, disperse it in a phosphate buffer, add the silk fibroin antibody and shake it, then add Tris-BSA, shake it and wash it to obtain specific magnetic beads, which are dispersed in a phosphate buffer; Step 5: Take the nano-CuO obtained in step 1 and treat it in PBS by ultrasonication, add silk fibroin antibody, shake it, freeze centrifuge the obtained product, remove the upper clear liquid, disperse it in PBS, freeze centrifuge it again, remove the lower substrate, add BSA solution, mix and react, and obtain specific nano-CuO; Step 6: Add the obtained specific magnetic beads and specific nano-CuO to the silk fibroin solution to be detected, incubate with shaking, remove the supernatant after centrifugation, place in hydrogen peroxide, and pass the obtained oxygen into the pressure sensor.
2. The method according to claim 1, characterized in that Step 1 is specifically as follows: dissolving CuCl2·2H2O in water containing 0.5-1.5wt% CuCl2, the concentration of which is 0.5-1.5wt%, to obtain a mixed solution, and dispersing it uniformly by ultrasonication; separately dissolving NaOH in water containing 0.5-1.5wt% PEG, to obtain a mixed solution, the concentration of which is 8-12mg / mL, and dispersing it uniformly by ultrasonication; mixing the two mixed solutions, further ultrasonically treating them, adding excess ethanol, and standing them overnight; washing the resultant with anhydrous ethanol and water in turn, and titrating with AgNO3 solution until Cl -1 Completely remove; then centrifuge the product, keep the product at 90-100℃ for 10-20h, grind it into powder, and calcine it at 350-450℃ to obtain nano CuO.
3. The method according to claim 1, characterized in that Step 2 is specifically as follows: weigh 5-6g FeCl3·6H2O and 2-4g FeSO4·7H2O and dissolve them in 100mL water, and stir until dissolved under nitrogen protection; add 3-5g NaOH, and continue stirring in a 70-90°C water bath for 0.5-1.5h to obtain Fe3O4 magnetic nanoparticles; weigh 180-220mg Fe3O4 magnetic nanoparticles in a container, add 15-20mL concentrated nitric acid, ultrasonicate for 10-30min, then wash with water, add 15-25mL anhydrous ethanol, 35-45mL water and 3-5mL ammonia water, and then ultrasonicate for 10-30min, take out, slowly add 3-4mL TEOS dropwise while stirring, continue stirring for 3-5h, then wash with ethanol and water successively, vacuum dry at 55-65°C for 1-3h to obtain nanomagnetic beads, and store them in phosphate buffer solution.
4. The method according to claim 1, characterized in that Step 3 is specifically as follows: 0.3-0.5 g of nanomagnetic beads are placed in a container, 15-25 mL of water is added, ultrasonic dispersion is uniformly performed, 8-12 mL of chloroform, 2-3 mL of anhydrous ethanol are added, and then 0.3-0.7 g of acrylamide, 0.8-1.2 mL of acetonitrile and 2-3 mL of methacrylic acid are added, and rapid stirring is performed at room temperature for 10-30 min. After sufficient mixing, 0.08-0.12 g of initiator azobisisobutyronitrile is added, and rapid stirring is performed at 40-50° C. for 6-8 h. Solid-liquid separation is performed using an external magnetic field, and the beads are repeatedly washed with anhydrous ethanol and water until excess organic matter is washed away to obtain functionalized nanomagnetic beads. The beads are placed in 350-450 uL PBS to obtain a functionalized nanomagnetic beads dispersion.
5. The method according to claim 1, characterized in that Step 4 is specifically as follows: take 80-120uL of functionalized nanomagnetic bead dispersion in a centrifuge tube, wash with phosphate buffer solution, and redisperse in 350-450uL phosphate buffer solution; add 250-350uL of EDC / NHS mixed solution to the obtained dispersion, activate the reaction at room temperature by shaking for 0.5-1.5h, wash with phosphate buffer solution, disperse in 400-600uL phosphate buffer, add 8-12uL silk fibroin antibody, shake at 25-30℃ for 0.5-1.5h, then add 80-120uL Tris-BSA, shake for 0.5-1.5h and then wash to obtain specific magnetic beads, which are dispersed in 300-500uL phosphate buffer.
6. The method according to claim 5, characterized in that In step 4, the pH value of the phosphate buffer solution is 7.4, and the usage ratio of MES, NaCl, EDC, and NHS in the EDC / NHS mixed solution is (0.3-0.5) g: (0.4-0.6) g: (15-25) mg: (20-30) mg.
7. The method according to claim 1, characterized in that Step 5 is specifically as follows: 0.8-1.2 mg of the nano-CuO obtained in step 1 is ultrasonically treated in 0.8-1.2 mL PBS for 0.5-1.5 h, 80-120 uL of silk fibroin antibody is added, and the mixture is shaken for 3-5 h. The obtained product is centrifuged and the upper clear liquid is removed, and the mixture is dispersed in 0.8-1.2 mL PBS. The product is centrifuged and the lower substrate is removed, and 300-500 uL of 2-4 wt% BSA solution is added, and the mixture is mixed and reacted for 20-40 min to obtain specific nano-CuO.
8. The method according to claim 1, characterized in that Step 6 is specifically as follows: adding the obtained specific magnetic beads and specific nano-CuO to the silk fibroin solution to be detected, incubating with shaking at 30-40°C for 1-3h, removing the supernatant after centrifugation, placing in hydrogen peroxide, and passing the obtained oxygen into the pressure sensor.
Citation Information
Patent Citations
Ferroferric oxide immunonanomagnetic bead, and preparation method and application thereof
CN107132346A
Nano magnetic bead for detection of rice insecticidal protein and detection method
CN107607705A